O(s) obscuro(s) dizer(es) de mães sobre o autismo de seus filhos - Telles, Cynara Maria Andrade (2011)
Listening to the mothers of autistic children is the aim of this work in order to look, at the materiality of these discourses, new senses and meanings to the pathology of autism and the (non) place given to mothers at the scientific universe. Through interviews, we undertook an interpretive gesture of the subjects discoursive singularity using as theoretical framework the french Discourse Analysis, which takes his place on the science being supported by the materiality of the spoken and written language that is documented by the mankind and contextualized in a specific historical process. The Discourse Analysis is a subject of interpretation whose methodology is working the circularity of a discourse that has already said, with senses that have already made legitimate, before and somewhere and the possibility of opening new meanings through the drift, the paraphrase and the metaphor. The aim of this work was to explore, by the listening of these mothers, some issues involving the subject and its discursive positions, from a particular social and historical context and set in the universe of language, considering the subject proposed by the Discourse Analysis as the main concept of this work. The interest in the subject emerged from the experience in an institution that served cases of children s mental illness, and the listening of the mothers stories happened through the difficulty to involve them in the work with their children, which it began with the diagnosis and was followed by clinical and pedagogical treatment. It was observed that, in the course of time and after the diagnosis, the mothers put their autistic children in the focus of their lives and together with the institution, they needed to do their reports on the child. The most of them stopped working, the relationship with their husband had serious difficulties, the attention to the other children was affected and the hope of a big improvement was running out. In most cases, the mothers were responsible for the work of their children in school, however, they almost didn t take part in the treatment. We noticed the effects of a discourse of authority (the scientific discourse) on the discourse of mothers, who weren t licensed to know about the problem, as well as the silencing of their dreams and desires; When these women were deprived of their place of exemplary mother, loving wife and woman they started protecting themselves against the pain through the denial, repeating the gesture of their autistic children. The interest in listening to these mothers has increased when we consider the term "refrigerator mothers" after the publication of the first work about the issue whose author was Leo Kanner, the first researcher who defined the pathology of autism as an isolated aspect, describing the mothers of these children as emotionally cold. In this metaphor, we observe an effect of sense on this subject-mother determining by the memory a discursive formation that has been causing effects of freeze of its discourses, which can be evidenced by scarce specialized treatment centers for cases of autism that orient themselves in humanistic theories; on the other hand, there is a growing trend in works that are based on organicist theories and lead to a larger deletion of a place of legitimacy for these mothers. Three discursive entries were selected for the analysis, the first one was the listening of mothers childhood memories about their relationships with family, the marks of this period that have determined the ways how their love choices were meant and which in turn constitute the second entry that broaches the mothers discourses about their wishes to compose their families; lastly, the third one was the listening of the effects of the child s diagnosis, because it s interesting for some researchers to investigate the previous history of autistic children like the ways how they were meant and put in discourse before and after of their birth.